Regulasi dan Peran Apoteker Dalam Menjamin Keamanan Obat Pada Apotek Online (E-Pharmacy) : Review - Hidayatullah Hidayatullah; Tri Mayasari; Elis Susilawati (UNIVERSITAS MUHAMMADIYAH MATARAM, 2026)
Digital health transformation has led to rapid growth in e-pharmacy, but it has also created security gaps due to the slower development of regulatory infrastructure compared to the pace of technological innovation. This study aims to analyze the integration of policies, the strategic role of pharmacists, and medication safety assurance within the digital ecosystem using a Systematic Literature Review (SLR) approach. Following the PRISMA protocol, the research synthesizes 27 relevant articles from global and national databases over the past seven years. The analysis reveals a critical gap between technological innovation and regulatory frameworks, which increases the risk of counterfeit drug circulation. The success of the system heavily depends on the synchronization of the Pharmaceutical Electronic System (PSEF) regulations, standardization of telepharmacy protocols, and the use of automated verification technologies to reduce medication errors. This study highlights that pharmacists must transform into digital gatekeepers by integrating a digital ethics framework and AI-based decision support systems. This transformation is essential to ensure patient safety in an anonymous, cross-border e-commerce environment. In conclusion, strengthening the professional role and implementing adaptive regulations are necessary to address future challenges in pharmacy.